Soteriologi dalam Bhagavad Gītā - Jelly, Ni Kadek; Saitya, Ida Bagus Subrahmaniam; Kurniarini, Ni Nyoman Yunike (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Bhagavad Gītā, which is part of the Bhishmaparva and also part of the epic Mahabharata, is the most famous religious poem in Sanskrit literature. The Bhagavad Gītā was chosen as the object of research study because the Bhagavad Gītā emphasizes the knowledge of God Almighty, namely the teachings of salvation or soteriology which contains the ultimate goal of human life. The problem formulation found in this research is related to the form, function and meaning of soteriology in the Bhagavad Gītā. This research uses the theory of Hermeneutics. The method used in this study is a qualitative research method with several stages, namely: determining the type of research, looking for data sources both primary and secondary data, determining research instruments, collecting data using literature study methods, document studies, observation methods, and online data search methods. The forms of salvation teachings or soteriology in the Bhagavad Gītā consist of Bhakti Marga Yoga, Karma Marga Yoga, Jnana Marga Yoga, and Raja Marga Yoga. The function of soteriological teachings in the Bhagavad Gītā is that it has two functions, namely a religious function and a social function. And the meaning of soteriology in the Bhagavad Gītā has the meaning of theology, namely God who is seen in the form of Nirguna Brahman and Saguna Brahman. The meaning of Cosmology is that everything that exists comes from God and will be preserved and returned to God. And the meaning of liberation is that it can be achieved if you let go of all the results of worldly actions and ties and by practicing the spiritual path, namely yoga, focusing your mind on God.